Central pontine myelinolysis and localized fluorodeoxyglucose uptake seen on 18 f-FDG PET/CT - Frederik Rønne; Peer Tfelt-Hansen; Lene Rørdam (World Journal of Nuclear Medicine)
Case report describing the finding of central pontine myelinolysis (CPM) using combined fluorine-18 ( 18 F)-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT). The patient was a known alcoholic who, during admission was under treatment for hyponatremia, showed a significant decline in both motor and cognitive function. Combined 18 F-FDG PET/CT showed localized FDG uptake in the pons, consistent with the finding of CPM observed on magnetic resonance imaging (MRI). CPM is a demyelinating lesion of the pons, resulting in several neurological symptoms. The exact cause of CPM is not clear, but a strong relations between loss of myelin and osmotic stress exists, especially during rapid correction of hyponatremia. The osmotic stress is thought to induce disruption of the blood-brain barrier, allowing access for inflammatory mediators in extravascular brain tissue, which most likely attracts glial cells of the brain, attracts macrophages and activates astocytes. We suggest that metabolism in these activated cells could be responsible for the localized FDG uptake during active CPM.